2018
DOI: 10.1111/cts.12561
|View full text |Cite
|
Sign up to set email alerts
|

Health Research Participation, Opportunity, and Willingness Among Minority and Rural Communities of Arkansas

Abstract: Prior research suggests that rural and minority communities participate in research at lower rates. While rural and minority populations are often cited as being underrepresented in research, population‐based studies on health research participation have not been conducted. This study used questions added to the 2015 Behavioral Risk Factor Surveillance System to understand factors associated with i) health research participation, ii) opportunities to participate in health research, and iii) willingness to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
1
11
1
Order By: Relevance
“…To achieve diversity in biomedical research participation, health systems including safety‐net systems serving diverse populations need to have the capacity and willingness to engage with research at the institutional level. As noted in prior studies, lack of access to research‐intensive academic medical centers limits access to cutting‐edge research that potentially could reduce health disparities …”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…To achieve diversity in biomedical research participation, health systems including safety‐net systems serving diverse populations need to have the capacity and willingness to engage with research at the institutional level. As noted in prior studies, lack of access to research‐intensive academic medical centers limits access to cutting‐edge research that potentially could reduce health disparities …”
Section: Discussioncontrasting
confidence: 68%
“…This finding also underscores the importance of outreach and community engagement to increase awareness of biomedical research, including donating biospecimens because it may impact the likelihood of participating among those who are not diagnosed with cancer. It also highlights the need and, whenever possible, the opportunity for academic health and cancer centers to conduct community‐based biomedical research in the communities that they serve and not just in the clinic . This requires strong community partners who together with academic health centers and cancer centers can develop, implement, and test innovative strategies around outreach and engagement to bolster awareness and diversity in biomedical research participation, advance research, and reduce cancer disparities …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building upon previous studies that suggested that women are less likely to share private social media information [20], we hypothesized that women would be less likely to share passive data as well. Although relevant research findings are mixed [21], we hypothesized that people of racial minority groups, compared with whites, would be less likely to share, given similar research on health research participation (eg, a study investigating African American participation [22]). Finally, on the basis of research on age and interest in mental health apps [23], we hypothesized that older patients would be less willing to share passive data.…”
Section: Introductionmentioning
confidence: 99%
“…A 2015 focus group study done by the same group in South Carolina showed that rural residents believed that clinical trials involved deception more often than urban residents and expressed that their participation would depend on whether their doctor recommended it or whether the trial would benefit a family member's health [8]. A 2018 Arkansas study showed that 45% of adults would be willing to participate in health research and rural respondents did not differ from urban respondents on this, though only 8.5% of rural respondents reported that they had participated in research [9]. Nation-wide data on the actual inclusion of rural OAs in research are lacking.…”
Section: Introductionmentioning
confidence: 99%